ANALISIS PEMBELAJARAN KELUARGA BERENCANA MAHASISWA PRODI DIII KEBIDANAN - Noor Azizah; Ana Zumrotun Nisak; Atun Wigati (Jurnal Ilmu Keperawatan dan Kebidanan, 2020)
Learning or support is basically an activity that is organized so that students learn. Adult learning methods that make learning a learning center or Student Center Learning (SCL). Process standards relating to the learning process, planning the learning process, implementing the learning process and learning burden on students.Descriptive qualitative research methods The subjects of this study are students and lecturers. The informant taking technique used was purposive sampling. Snowball sampling technique. Data collection methods in this study, interviews, observation and study documentation. Analysis of the data of this study uses an interactive model through data reduction, displaying data, concluding and gathering conclusions.Results: Planning the learning process of the family planning course, which is making a semester learning plan. This RPS contains course descriptions, learning achievements, subjects, instructional methods, structured assignments and discussions. RPS is prepared in accordance with the development of science and technology. The theory learning process using the Student Center Learning (SCL) method of lecturers as facilitators and motivators in family learning planning methods used are cooperative learning and Problem Based Learning (PBL). Laboratory learning uses role play and demonstration models. Assessment on learning theory is midterm, final semester examination and structured assessment assignment. Learning laboratory assessment list.It takes a combination of learning methods and laboratories so that students are not bored and are more interactive so that learning outcomes are more optimal.